Competing Conversations: An Examination of Competition as Intrateam Interactions - Abraham, Elsheba K.; McCusker, Maureen E.; Foti, Roseanne J. (Frontiers in Psychology, 2019)
Intrateam competition is an inherently social and interactional process, yet it is not often studied as such. Research on competition is mostly limited to studying it as an individual state and assumes that the resulting team outcomes are equivalent across different competition types. Often overlooked in competition research are the means through which competition can lead to constructive outcomes for the team. Constructive competition occurs when the primary motivation is not to win at the expense of others, but rather to make social comparisons and gain knowledge of relative competence. This study furthers insight into constructive competition by studying its interpersonal characteristics as it develops within a team, and its impact on task conflict, perceived performance, and team satisfaction. The conversations of 24 student project teams were recorded over 4 weeks and analyzed, operationalizing competition as an attempt to exert control and influence on the team. Each individual then provided sociometric ratings of perceived performance of each team member, and rated the level of task conflict and satisfaction of the team. The effects of competition on perceived performance and team satisfaction, both directly and indirectly through task conflict, were examined. Findings demonstrated a negative direct effect of competition on the range of perceived performance ratings, and a positive indirect effect of competition on team satisfaction as mediated through task conflict. The study broadens understanding on the construct of competition and underscores the positive implications competition can bring to the teams.